Successful outcome of open distal interphalangeal joint luxation in equids treated by surgical debridement without internal implants - L. C. Ferrari; E. V. P. Apolonio; S. L. de Oliveira-Gonçalves; A. L. A. Rambo; J. V. Bergamasco; J. M. Alonso; M. J. Watanabe; A. L. G. Alves (Veterinary Research Communications, 2026)
Introduction The distal interphalangeal joint (DIPJ) plays a crucial role in the function of the hoof and digit. Dislocations and subluxations in this region are rare and primarily of traumatic origin. Case Report This case report aims to describe two unusual cases of open DIPJ dislocation, including clinical presentation, diagnostic workup, treatment, and long-term follow-up. Both animals presented with open traumatic distal interphalangeal joint (DIPJ) luxation. In Case 1, the animal received initial care on the property 5 h post-trauma and presented with joint exposure and articular surface contact with the ground. In Case 2, the animal was referred to the veterinary hospital without prior care, 3 h post-trauma, but there was no contact of the articular surface with the ground. Both animals showed grade 5/5 lameness (AAEP). The animals underwent general anesthesia, joint lavage, regional intravenous perfusion with antibiotics, debridement of devitalized tissues, skin synthesis, and immobilization with synthetic casting. During immediate recovery and hospitalization, a grade 4/5 lameness persisted. Long-term radiographic control revealed the development of degenerative joint disease in both animals. After 3 and 2 years, respectively, animals 1 and 2 showed persistent lameness (grade 2/5) with an absence of local sensitivity. Conclusion The conservative treatment employed in these cases of open DIPJ luxation proved effective for the maintenance of the patients’ lives, and although the infectious pathological process invariably progressed to osteoarthritis, the evolution of the clinical conditions allowed for light exercise and maintenance of reproductive activity.

Predicting hairy vetch (Vicia villosa Roth) biomass across climatic gradients: A tool for sustainable cover crop management - Juan P. Renzi; Petr Smýkal; Ignacio Ducos; Aldana Alonso; Clara Llorens; Guillermo García; Jone Irazusta; Jan Brus (Agricultural Systems, 2026)

Chiral resolution of profoxydim: Implications for herbicidal efficacy and ecotoxicological assessment - A. Cervantes-Díaz; M.J. Patiño; P. Sánchez-Argüello; J.L. Alonso-Prados; M.I. Santín-Montanyá; P. Sandín-España (Environmental Pollution, 2026)

Farmers' attitudes towards biodiversity shape the effectiveness of biodiversity-friendly management practices for wild bees, but not plants and spiders - Jeroen Scheper; David Kleijn; Fabian Klebl; Anneli Adler; András Báldi; Ignasi Bartomeus; Vincent Bretagnolle; J.P. Reinier De Vries; Sabrina Gaba; Maura Ganz; José M. Herrera; Felix Herzog; et al. (Biological Conservation, 2026)

From fable to fact: empirical evidence of ecological and behavioral interactions between foxes and skunks - César P. Ley-Quiñónez; Emilio Rendón-Franco; Edna Meza-González; Catherine E. Hart; Jesús G. Ortega-Anaya; Renato Leal-Moreno; Ricardo J. Aguilar-Romero; Ana B. Isaak Delgado; A. Alonso Aguirre; Alan A. Zavala-Norzagaray (Mammal Research, 2026)

Development of a quadruple isotope spiking methodology to study mercury methylation and methylmercury demethylation in environmental and biological media - Javier Garcia-Calleja; Pablo Rodríguez-González; Laura Suárez Criado; Emmanuel Tessier; João P. Santos; Sylvain Bouchet; Zoyne Pedrero; Vera I. Slaveykova; J. Ignacio García Alonso; David Amouroux (Analytica Chimica Acta, 2026)

ShellBank: traceability toolkit and global database of marine turtle DNA - Michael P. Jensen; Greta J. Frankham; Carla Alonso O’Friel; Erin L. LaCasella; Kelly I. Morgan; Maftuna Sola; Lucy M. I. Webster; Peter H. Dutton; Christine A. Madden (Frontiers in Marine Science, 2026)
Effective conservation and enforcement strategies for marine turtles depend on understanding population structure, connectivity, and the geographic origins of turtles impacted by threats such as bycatch, overexploitation, and illegal trade. However, mitochondrial DNA (mtDNA) data remain fragmented across studies, with inconsistent sequence lengths, haplotype nomenclature, and metadata standards limiting their application in conservation, management, and wildlife forensics. To address these challenges, we developed ShellBank, a global marine turtle genetic traceability toolkit and open-access mtDNA database that consolidates and standardizes more than 20,000 mtDNA control-region sequences from published literature and verified contributed datasets. The platform harmonizes sequence lengths, haplotype nomenclature, and associated metadata, and provides tools to search haplotypes, access population-level baselines, extract frequency tables for Mixed Stock Analysis (MSA), and explore connectivity among nesting, in-water, and trade datasets. We demonstrate its utility through two case studies. First, mtDNA from a tortoiseshell seizure in the United Kingdom was compared against the ShellBank baseline, identifying likely source rookeries in the Eastern Caribbean and highlighting priority sampling gaps. Second, reanalysis of a hawksbill turtle foraging aggregation on the Great Barrier Reef using an expanded reference baseline substantially altered previous stock assignment estimates, corroborated flipper-tag and satellite-tracking data, and confirmed multi-stock connectivity across the western Pacific. By centralizing and standardizing global marine turtle mtDNA data, ShellBank improves the resolution, accuracy, transparency, and application of genetic traceability for conservation, management, and enforcement, strengthening the ability of researchers, managers, decision-makers, and enforcement agencies to identify source regions, detect population-level impacts, understand ecological connectivity, and guide evidence-based conservation actions.

OC7 phase I: CFD investigation of viscous forces on rectangular members of semisubmersibles - Yingqian Liao; Lu Wang; Amy Robertson; Jason Jonkman; Arjen Koop; Guillén Campaña-Alonso; Daniele Aromatario; António Maximiano; Hannah Darling; David P. Schmidt; Shengbai Xie; Jasim Sadique; et al. (Ocean Engineering, 2026)

Beyond heavy metals: Integrating safety and agronomic performance in the classification of organic amendments - A. Moreno-Robles; P. Souza-Alonso; D. Silva-Abilleira; S. García Martín; R.M. Peña Crecente; J. Barciela García; J.M. de la Rosa; V. Piñeiro; A. Merino; C. Herrero-Latorre (Journal of Cleaner Production, 2026)

Miscellaneous chorological, nomenclatural and taxonomic notes on Carex (Cyperaceae) from South America, including the description of three new species - P. Muñoz-Schüler; J. I. Márquez-Corro; A. Cano; A. Camilo; M. Corvalán-Favereau; S. Gebauer; I. Larridon; P. Mazzei; P. Mendoza-Babilón; D. Montesinos-Tubée; A. Morales-Alonso; N. Oleas; et al. (Kew Bulletin, 2026)
Summary Despite the ongoing intensive efforts on disentangling the diversity of the genus Carex (Cyperaceae) in South America, there is much still to be accomplished. In this note we studied collections from some of the main South American and North American herbaria, new field collections, and observations from the citizen platform iNaturalist, to report chorological, nomenclatural, and taxonomic notes for 16 South American Carex species. These include comments on invasive species, novel national reports for five species, including the first report of Carex echinata to the continent, the clarification of the use of the name Carex peruviana and the exclusion of Carex vixdentata from the Peruvian flora, and the description of three new species from the Northern Andes and the Peruvian desert: Carex guaguarum Jim.Mejías & Muñoz-Schüler, Carex ros-desertum Jim.Mejías & Muñoz-Schüler (subg. Vignea , sect. Bracteosellae ), and Carex via-montana A.Mor.Alons. & Jim.Mejías (subg. Psyllophorae , sect. Junciformes ).

Unravelling a Rapid Radiation: Biogeography and Niche Evolution of Carex sect. Echinochlaenae Kük . (Cyperaceae) - A. Morales‐Alonso; K. A. Ford; M. Sanz‐Arnal; M. Míguez; P. García‐Moro; T. Villaverde; P. Jiménez‐Mejías; S. Martín‐Bravo (Journal of Biogeography, 2026)
Aim Carex section Echinochlaenae has a disjunct distribution across the Southern Hemisphere. It displays a clear center of diversity in New Zealand coupled with extreme morphological and ecological diversification, suggesting a potential evolutionary radiation. We aimed to reconstruct the biogeographic history of the group and evaluate bioclimatic niche evolution during colonization and diversification events. Location Southern Hemisphere, with emphasis in New Zealand. Taxon Carex section Echinochlaenae (subgen. Carex , Cyperaceae). Methods An integrative approach combining phylogenetic‐phylogenomic, biogeographic and bioclimatic data was used. We reconstructed a Hyb‐Seq phylogenomic backbone, as well as an expanded Sanger‐based phylogeny (ITS, ETS, matK). We investigated the biogeographic history of the group's Trans‐oceanic dispersal across the Southern Hemisphere through ancestral area reconstruction. Bioclimatic niche evolution was explored at different spatio‐temporal scales by modelling environmental space for close sectional lineages ( Distantes , Africanae , Echinochlaenae ) and for disjunct areas within Echinochlaenae . Results Both Sanger‐based and phylogenomic reconstructions retrieved a monophyletic sect. Echinochlaenae , but with low internal resolution, topological incongruences and conflicting genomic concordance factors (low gCF vs. moderate‐high sCF values) affecting certain key nodes. The lineage dates back to the Early Late Miocene (c. 10.7 mya), while cladogenesis is concentrated around the Miocene–Pliocene boundary. Abiotic niche space of the group in New Zealand was relatively similar both between closely related sections and disjunct areas in sect. Echinochlaenae . Main Conclusions The complex evolutionary relationships and their ecomorphological differentiation in New Zealand are compatible with a rapid radiation process likely involving mechanisms that rapidly increase genetic diversity and are probably responsible for the lack of phylogenetic signal even though it is a relatively ancient radiation. New Zealand acted as the ancestral area and hub of in situ diversification for this lineage, and as a source of recurrent dispersal events shaping its disjunct distribution. Abiotic niche conservatism predominates across large evolutionary and geographic scales. Given the disjunction from its closest relatives, this suggests that niche amplitude is determined by internal constraints.

Isolation and partial characterization of OmpF and LsrB as putative Actinobacillus seminis testosterone receptors - Gerardo A. Ramírez-Paz-y-Puente; Martha O. Salcedo-Álvarez; Miguel A. Avalos-Rangel; Candelario Vázquez-Cruz; Elena Cobos-Justos; Patricia Sánchez-Alonso; Edgar Zenteno; Erika P. Meneses-Romero; Erasmo Negrete-Abascal (World Journal of Microbiology and Biotechnology, 2026)

Production of precursors for sustainable aviation fuels through furfural/cyclopentanone aldol condensation boosted by TiO2-loaded dendritic ZSM-5 catalysts - Daniel de la Calle; Jennifer Cueto; María del Mar Alonso-Doncel; Rafael A. García-Muñoz; David P. Serrano (Fuel, 2026)

Bioacoustic Baselines for Intact Forests - Z. Buřivalová; S. Perea; L. M. Berman; H. S. S. C. Sagar; T. M. Maeda; N. Yoh; G. Ingram; M. Persche; C. Mere‐Roncal; A. Lopera‐Toro; E. Chaboteaux; R. Rumelt; et al. (Global Change Biology, 2026)
Forests are at the frontline of both climate and biodiversity crises: forests are fundamental to the regulation of Earth's atmospheric carbon dioxide levels, and tropical forests alone harbour over half of all terrestrial species. Consequently, forests are at the centre of global efforts to both prevent extinctions of species and sequester carbon to mitigate climate change. Most carbon sequestration initiatives do not measure how effective they are in terms of biodiversity protection, largely because it is expensive, complex and often not required. Compounding this problem is the lack of reliable biodiversity baselines, against which positive changes due to conservation and negative changes due to human pressure could be measured. The Soundscape Baselines Project is a global initiative to collect and analyse bioacoustic baselines in some of the world's remaining intact forests. The baseline data are collected using a modular system of passive acoustic monitoring and ancillary data that can be expanded and integrated with other technologies. It is managed by local teams of scientists, conservation practitioners and community members. Emphasis is on the usability of data and equipment beyond the project, community engagement and building an interconnected network of scientists across forested countries, particularly historically underexplored partnerships between tropical forest countries. In this paper, we describe the initiative and share initial results to demonstrate how the project could be used for biodiversity conservation purposes in the future and outline steps towards operationalization. We also draw a list of priority areas for additional baseline locations across remaining intact forests. We discuss how bioacoustic baselines established now and in the future will become invaluable in a rapidly changing climate and the resulting unprecedented change in Earth's forests. Establishing rigorous biodiversity baselines using bioacoustics and other technologies and approaches through collaborative science is fundamental to ground biodiversity conservation in evidence, equity and transparency.

Folding of unconformable sequences in the Argentine Precordillera. Strain compatibility problems and resulting accommodation structures - J.L. Alonso; J. Gallastegui; L.R. Rodríguez Fernández; J. García-Sansegundo; N. Heredia; P. Farias; L. Quintana; R. Cardó; V.A. Ramos (Journal of Structural Geology, 2026)

Genetic testing for hereditary breast and ovarian cancer in the Murcian population using a comprehensive NGS panel - Y. Mestre Terkemani; L. Rosado Jiménez; A. García Aliaga; M. D. Sarabia Meseguer; M. Marín Vera; J. A. Macías Cerrolaza; P. Sánchez Henarejos; M. R. García Hernández; M. Zafra Poves; B. Alvarez Abril; E. García Torralba; C. B. López Sánchez; et al. (Familial Cancer, 2026)

Isomerization of α- and β-pinene epoxides over dendritic ZSM-5 zeolites - Carina Mosquera; Luis A. Gallego-Villada; Marta Mediavilla; Jennifer Cueto; Maria del Mar Alonso-Doncel; Edwin Alarcón; David P. Serrano (Chemical Engineering Journal, 2026)

Per- and polyfluoroalkyl substances (PFAS) transport from biosolids-amended soils: An experimental and numerical approach - Alonso Doria-Manzur; Evan P. Gray; Summer S. Streets; Jennifer L. Guelfo (Water Research, 2026)

Insight into origin and transformation of dissolved organic matter under contrasting nutrient conditions on the Northern Patagonian Continental Shelf, Southwestern Atlantic Ocean - John E. Garzón-Cardona; Ana M. Martínez; Cecilia Alonso; Elbio D. Palma; María B. Gonzalez; Facundo M. Barrera; Lisandro A. Arbilla; Azul S. Gilabert; Ana L. Delgado; Boris P. Koch; Bernd Krock; M. Celeste Lopez-Abbate; et al. (Marine Environmental Research, 2026)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Insights into the transformation of alloxydim during chlorination process; by-product identification, DFT calculations and ecotoxicological assessment - M. Cobos-Escudero; A. Cervantes-Díaz; J.C. Nieto-Carmona; J. Pro; P. Sánchez-Argüello; M. Alcamí; Al Mokhtar Lamsabhi; J.L. Alonso-Prados; P. Sandín-España (Science of The Total Environment, 2025)

Dynamic life cycle assessment of climate change impacts of hydrogen production from energy crops - L. Romero-Piñeiro; A.L. Villanueva-Perales; B. Alonso-Fariñas; P. Haro (Science of The Total Environment, 2025)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Revealing Chronotypes Across Aquatic Species Using Acoustic Telemetry - Martina Martorell‐Barceló; David Abecasis; Mourad Akaarir; Alexandre Alonso‐Fernández; Robert Arlinghaus; Eneko Aspillaga; Margarida Barcelo‐Serra; Niels W. P. Brevé; Jan G. Davidsen; Antoni Gamundí; Amalia Grau; Bernat Hereu; et al. (Fish and Fisheries, 2025)
Acoustic telemetry offers valuable opportunities to investigate individual variability in circadian‐related and other behaviours and how environmental cues shape these patterns in wild fish populations. However, this potential has not yet been fully exploited. We conducted a meta‐analysis on 44 datasets from 34 distinct marine and freshwater species and different types of data (acoustic detections, depth, acceleration and positioning). Our aim was to explore the potential of acoustic telemetry in identifying chronotypes as consistent among‐individual differences in circadian‐related behaviours. First, we applied hidden semi‐Markov models to classify individual time series into active and rest states. Subsequently, we computed two classical circadian‐related behavioural traits: awakening time (as the activity onset) and rest onset (as the activity offset). Subsequently, we identified distinct phenotypes by decomposing behavioural variation into within‐ and among‐individual components based on repeatability scores. We found evidence of distinct chronotypes in 17 species, with average repeatability scores of 0.52 for awakening time and 0.43 for rest onset, revealing that chronotypes are common in aquatic species. Our findings highlight that both the data type, particularly acceleration sensors, and the number of detections are effective tools for exploring chronotypes. Our study proposes a novel approach to characterising daily activity patterns in aquatic species, predominantly in fishes, and provides guidelines for investigating chronotypes across diverse taxa. We emphasise the promise of biotelemetry and advanced statistical models for improving our understanding of the behaviour of aquatic species and highlight the value of synthesising across large data sets collected in networks of biotelemetryprojects.

Intratumoural CPMV immunotherapy in a case of canine inflammatory mammary cancer - G. Valdivia; A. Alonso-Diez; L. Barreno; J. Affonso de Oliveira; G. Ortiz-Diez; M. Suarez; P. García-San José; N. Steinmetz; S. Fiering; M. Pérez-Alenza; L. Peña (Journal of Comparative Pathology, 2025)

Deadly serratia marcescens infection in a bottlenose dolphin (Tursiops truncatus) - A. Reyes-Matute; A. Jesús Fernández Rodríguez; J. Luis Martín Barrasa; J. Vicente Guerra Garcés; A. Román Gutiérrez Llanos; P. Alonso Alomorox; M.A. Arbelo Hernández (Journal of Comparative Pathology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Anti-nervous necrosis virus activity of the growth hormone releasing peptide-6, GHRP-6 - Daniel Álvarez-Torres; Rebeca Martínez; Patricia Moreno; M. Carmen Alonso; Esther García-Rosado; Mario P. Estrada; Julia Béjar (Aquaculture International, 2025)
Growth hormone-releasing peptide 6 (GHRP-6), is a six-amino acid synthetic peptide that acts as a ghrelin analog and has shown growth-promoting and immunomodulatory activities in several fish species. This study evaluates the effects of GHRP-6 against the infection with the nervous necrosis virus (NNV), an important pathogen affecting the central nervous system of a wide range of fish species, including European seabass ( Dicentrarchus labrax ). For the in vitro evaluation, E11 cells were treated with GHRP-6 before and/or during viral infection, resulting in higher cellular survival rates, lower viral genome replication, and lower production of infective viral particles compared with control cells. These results indicate that GHRP-6 protects E11 cells from the viral infection. In order to conduct the in vivo evaluation, European seabass specimens were intraperitoneally injected with GHRP-6, resulting in the significant upregulation of several immune genes, such as TNF-A , RTP3 , and IgM , in head kidney and intestine. Furthermore, NNV replication was lower in the brain from GHRP-6 injected fish than in controls, and the brain antiviral immune response was clearly modulated in treated fish. These results support the potential of GHRP-6 as an antiviral compound that could contribute to prevent viral diseases in fish farms, a priority for the aquaculture industry.

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

Stable isotope analysis reveals inter- and intraspecific trophic relationships of the endangered Central American river turtle in southern Mexico - Eduardo Reyes-Grajales; Matteo Cazzanelli; Nora P. López-León; Alejandra Sepúlveda-Lozada; Luis Antonio Muñoz Alonso; Miriam Soria-Barreto; Rocío Rodiles-Hernández (Limnologica, 2025)

On the operation of a solar photo-Fenton demonstration plant: Effect of microcontaminant removal rate on cost and environmental impact - E. Gualda-Alonso; D. Rodríguez-García; P. Soriano-Molina; M.M. Pérez-Martínez; R. Martínez-Vázquez; J.L. García Sánchez; J.L. Casas López; J.A. Sánchez Pérez (Chemical Engineering Journal, 2025)

Effects of the invasive aquatic snail Potamopyrgus antipodarum (Gray, 1853) on ecosystem properties and services - Álvaro Alonso; Gonzalo A. Collado; Claudia Gérard; Edward P. Levri; Rodrigo B. Salvador; Pilar Castro-Díez (Hydrobiologia, 2025)
Ecosystems provide benefits to humans, including provisioning, regulating, and cultural services. However, invasive species can threaten ecosystem well-functioning and services provided. One invasive species with such potential is the New Zealand mud snail (NZMS) Potamopyrgus antipodarum . The aims of this study are focused on the quantitative review of (1) the NZMS impacts on ecosystem properties and their direct links with ecosystem services, and (2) the ecosystem services that can be affected by the NZMS. The high density reached by this species in most of the invaded ecosystems and its highly competitive ability affect ecosystem structure and functioning. However, some facilitation processes on native species may result in an improvement of some services. The NZMS tends to positively affect cultural services (88% positive cases) but negatively to provisioning services (77% of cases). Regarding, regulating and maintenance services, the proportions of positive and negative effects were similar (45% vs 36%, respectively). Therefore, the NZMS is a species with numerous negative impacts on ecosystem services. However, ecosystem services related to health (e.g., dilution effect against parasites) and research (e.g., biomonitoring) are cultural services that the NZMS can improve. No economic assessment of the impacts of the NZMS is available in the literature.

Contrasting behavioural responses to concurrent stressors in an aquatic snail: the importance of stress type and combination - Álvaro Alonso; MC Llandres-Díez; P. Cruces-Estepa (Ecotoxicology, 2025)

A Two-Decade Overview of the Environmental Carrying Capacity in Bahía Santa Maria–La Reforma Coastal Lagoon System - Omar Calvario-Martínez; Julio Medina-Galvan; Virginia P. Domínguez-Jiménez; Rosalba Alonso-Rodríguez; Miguel A. Sánchez-Rodríguez; Paulina M. Reyes-Velarde; Miguel Betancourt-Lozano; David Serrano-Hernández (Journal of Marine Science and Engineering, 2025)
Santa María Bay–La Reforma (SMBLR), with its 58,300 ha is one of Mexico’s most extensive estuarine lagoon systems. It is made up of islands, estuaries, and mangrove areas, which provide a vital part of the habitat and refuge of a significant number of birds, fish, amphibians, reptiles, and mammals. The fishing of blue and brown shrimp, marine and estuarine fish, as well as the exploitation of crab and bivalve mollusks, represent an important economic value for the communities that live there and for the state of Sinaloa, Mexico. This state ranked second in fisheries production and first in aquaculture production by 2023. However, the biological richness of this ecosystem has historically been threatened by economic activities such as agriculture, livestock, and aquaculture that, via watersheds, translate into continuous inputs of nutrients and other pollutants. This has led to modifications to the system such as changes in the structure of pelagic and benthic communities, mainly in response to eutrophication. To understand the dynamics of nutrient inputs to the ecosystem, this work presents a comparative analysis of the system’s carrying capacity and the magnitude of the main economic activities from 2007 to 2019. We found that during each season of the year and its transitions, the system functions as a nitrogen and phosphorus sink, which is associated with autotrophic net ecosystem metabolism and nitrogen fixation processes. We suggest that while water residence times in SMBLR are short, these are strongly influenced by the high volumes of water and nutrient loads determined by the spatio-temporal variations in hydrological drainage from the basins of influence of the system. The discharge of agriculture and aquaculture drains into SMBLR are areas of concern due to the high amount of nutrients. Although SMBLR is mostly an autotrophic system, there are signs that the carrying capacity during some seasons has been exceeded, and adverse ecological and socioeconomic effects in the basin are evident.

Enhanced production of jet fuel precursors via furfural/cyclopentanone aldol condensation by synergistic pairing TiO2 with nano-ZSM-5 zeolite - Jennifer Cueto; Daniel de la Calle; María del Mar Alonso-Doncel; Elena A. Giner; Rafael A. García-Muñoz; David P. Serrano (Bioresource Technology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Universally Adaptable Multiscale Molecular Dynamics (UAMMD). A native-GPU software ecosystem for complex fluids, soft matter, and beyond - Raúl P. Peláez; Pablo Ibáñez-Freire; Pablo Palacios-Alonso; Aleksandar Donev; Rafael Delgado-Buscalioni (Computer Physics Communications, 2025)

Hyphal swelling induced in the phagosome of macrophages - María Fernanda Alonso; Judith M. Bain; Lars P. Erwig; Alistair J.P. Brown; Neil A.R. Gow (Fungal Biology, 2024)

A Tropical Estuary Where Mercury Does Not Biomagnify and its Adjacent Waters that Render Extremely High Mercury Concentrations in Top Predators - Paulo R. Dorneles; Thaís de C. Paiva; Gabriel P. Bighetti; Dhoone Menezes; António M. B. Marques; Patricia S. L. Anacleto; Leonardo Flach; Fabíola H. S. Fogaça; Ana Paula C. Farro; Mariana F. Nery; Ana Lúcia Cypriano-Souza; Mirela D’arc; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of dihydrocarvone over dendritic ZSM-5 Zeolite: A comprehensive study of experimental, kinetics, and computational insights - Luis A. Gallego-Villada; Wander Y. Perez-Sena; Julián E. Sánchez-Velandia; Jennifer Cueto; María del Mar Alonso-Doncel; Johan Wärmå; Päivi Mäki-Arvela; Edwin A. Alarcón; David P. Serrano; Dmitry Yu. Murzin (Chemical Engineering Journal, 2024)

Periorbital necrotizing fasciitis: clinical perspectives on nine cases - David Oliver-Gutierrez; R. L. P. van der Veen; Elena Ros-Sánchez; Gloria Segura-Duch; Tirso Alonso; Alejandra Herranz-Cabarcos; Jessica Matas; Roberto Castro Seco; Miguel Ángel Arcediano; Miguel Ángel Zapata; Joan Oliveres (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Interaction of aluminum alloys with MKPC and Portland-based cements on the metal-matrix interface - C. Fernández-García; P. Padilla-Encinas; R. Fernández; M.C. Alonso (Applied Geochemistry, 2024)

OS02-11 Metabolic disturbances linked to metabolic disorders in in vitro and in vivo models exposed to PFOA: an integrated multi-omics analysis - N. Papaioannou; T. Papageorgiou; D. Schultz; I. Frydas; C. Gabriel; H. Le Mentec; D. Lagadic-Gossmann; T. Boronat-Belda; H. Ferrero; S. Karakitsios; S. Langouet; P. Alonso-Magdalena; et al. (Toxicology Letters, 2024)

Assessment of pathogenic protozoa in a drinking water treatment plant with UV treatment - L. Moreno-Mesonero; P. Soler; J.L. Alonso; V.J. Macián; Y. Moreno (Journal of Environmental Management, 2024)

What potential do mosses have as biomonitors of POPs? A comparative study of hexachlorocyclohexane sorption - Z. Chaos; J.A. Fernández; M. Balseiro-Romero; M. Celeiro; C. García-Jares; A. Méndez; P. Pérez-Alonso; B. Estébanez; J. Kaal; K.G.J. Nierop; J.R. Aboal; C. Monterroso (Science of The Total Environment, 2024)

Chemical and physical properties of sewage sludge as a substrate for tree seedlings - J. M. Alonso; É. F. M. Pinheiro; L. F. de Sousa Antunes; T. da Costa Lima; J. G. Ribeiro; P. S. dos Santos Leles (International Journal of Environmental Science and Technology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Influence of meteorological variables and air pollutants on measurements from automatic pollen sampling devices - M. González-Alonso; J. Oteros; M. Widmann; J.M. Maya-Manzano; C. Skjøth; L. Grewling; D. O'Connor; M. Sofiev; F. Tummon; B. Crouzy; B. Clot; J. Buters; et al. (Science of The Total Environment, 2024)

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Comparison of the blood biochemical values of foraging and nesting Olive Ridley turtles (Lepidochelys olivacea) from Sinaloa, Mexico - Jorge Valdés-Flores; César P. Ley-Quiñonez; Nidia León-Sicairos; Hector Flores-Villaseñor; Jorge Velázquez-Román; Uriel Angulo-Zamudio; Alan Zavala-Norzagaray; Catherine E. Hart; Vicente Olimón-Andalón; Renato Leal-Moreno; Ingmar Sosa-Cornejo; A. Alonso Aguirre; et al. (Marine Environmental Research, 2024)

Stereoisomeric separation of the chiral herbicide profoxydim and residue method development in rice by QuEChERS and LC–MS/MS - A. Cervantes-Díaz; M. Mateo-Miranda; N.H. Torrado-Cubero; J.L. Alonso-Prados; P. Sandín-España (Food Chemistry, 2024)

Degradation kinetics of sugars (glucose and xylose), amino acids (proline and aspartic acid) and their binary mixtures in subcritical water: Effect of Maillard reaction - P. Alonso-Riaño; A.E. Illera; O. Benito-Román; R. Melgosa; A. Bermejo-López; S. Beltrán; M.T. Sanz (Food Chemistry, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

The ability of donkey sperm to induce oocyte activation and mule embryo development after ICSI - Camila Arroyo-Salvo; Marïa Y. Cogollo Villarreal; Gabriel Clérico; Ana P. Flores Bragulat; Andrea Niño Vargas; Catalina Castañeira; Olinda Briski; Carolina Alonso; Jessica Plaza; Jose M. Zeledon; Luis Losinno; Marcelo Miragaya; et al. (Theriogenology, 2024)

Indoor radon risk mapping of the Canary Islands using a methodology for volcanic islands combining geological information and terrestrial gamma radiation data - C. Briones; J. Jubera; H. Alonso; J. Olaiz; J.T. Santana; N. Rodríguez-Brito; A.C. Arriola-Velásquez; N. Miquel; A. Tejera; P. Martel; E. González-Díaz; J.G. Rubiano (Science of The Total Environment, 2024)

Observations of river-wave interactions at a small-scale river mouth - Alonso Roco; Raúl P. Flores; Megan E. Williams; Gonzalo S. Saldías (Coastal Engineering, 2024)

Applications of bioclimatology to assess effects of climate change on viticultural suitability in the DO León (Spain) - S. del Río; R. Álvarez-Esteban; R. Alonso-Redondo; R. Álvarez; M. P. Rodríguez-Fernández; A. González-Pérez; A. Penas (Theoretical and Applied Climatology, 2024)
Spain accounts for 13.1% of the world’s vineyard area, and viticulture is crucial for the socioeconomic and cultural sectors. Vineyards are among the perennial crops that can suffer most negative impacts under climate change which can pose challenges to the sustainability of viticulture. Local and regional studies are needed to assess these impacts to help implement effective strategies in response to climate change. To this end, our approach involves integrating both conventional agroclimatic indices and those new bioclimatic indices that have proven to be essential for the characterization and demarcation of vineyards into species distribution models to assess areas suitable for viticulture under climate change projections. The proposed methodology was tested in a viticultural region located in northwestern Spain (DO León). An ensemble platform was used to build consensus models encompassing three general circulation models, two emission scenario pathways and two time horizons. Only the predictors that effectively characterize each grape variety were included in the models. The results revealed increases in the continentality index, compensated thermicity index, hydrothermic index of Branas, and temperature range during ripening in all the future scenarios analyzed in comparison to current conditions. Conversely, the values for the annual ombrothermic index and growing season precipitation may decrease in the future. The pattern of changes for 2070 will be more pronounced than for 2050. A significant loss of future habitat suitability was detected within the limits of the study area for the grape varieties analyzed. This negative impact could be counteracted to some degree with new and favorable areas for the cultivation of vineyards in territories located at the north of the DO limits. We suggest that our results could help policymakers to develop practices and strategies to conserve existing grape varieties and to implement efficient adaptation measures for mitigating or anticipating the effects of climate change on viticulture.

Assessing the effect of organic amendments on the degradation of profoxydim in paddy soils: Kinetic modeling and identification of degradation products - A. Cervantes-Díaz; E. Alonso-Prados; J.L. Alonso-Prados; P. Sandín-España (Science of The Total Environment, 2024)

Enhanced oil dehalogenation during catalytic pyrolysis of WEEE-derived plastics over Fe- and Ca-modified zeolites - Julio López; Lidia Amodio; Maria del Mar Alonso-Doncel; Jennifer Cueto; Hector Hernando; Michal Mazur; Jiří Čejka; Patricia Pizarro; David P. Serrano (Journal of Environmental Chemical Engineering, 2024)

Natural radionuclides as tracers of coastal sediment dynamics in El Confital Bay (Spain): Spatial distribution and relationships with sediment characteristics - A.C. Arriola-Velásquez; A. Tejera; I. Alonso; F. Cámara; M. Cantaluppi; H. Alonso; N. Miquel-Armengol; J.G. Rubiano; P. Martel (CATENA, 2024)

Empirical ground-motion relations of peak ground acceleration in the region of the Gulf of California - Gina P. Villalobos-Escobar; Raúl R. Castro; Tomás A. Peña-Alonso (Natural Hazards, 2024)

Atmospheric dependence of the direct, diffuse, and global clear-sky conversion ratios between solar photosynthetic active irradiance and photon flux - J.L. Di Laccio; P. Russo; A. Monetta; R. Alonso-Suárez; G. Abal (Agricultural and Forest Meteorology, 2024)

Soil properties determine the impact of nZVI on Lactuca sativa L and its rhizosphere - M. Gil-Díaz; J. Álvarez-Aparicio; J. Alonso; C. Mancho; M.C. Lobo; J. González; P. García-Gonzalo (Environmental Pollution, 2024)

Continuous solar photo-Fenton for wastewater reclamation in operational environment at demonstration scale - E. Gualda-Alonso; N. Pichel; P. Soriano-Molina; E. Olivares-Ligero; F.X. Cadena-Aponte; A. Agüera; J.A. Sánchez Pérez; J.L. Casas López (Journal of Hazardous Materials, 2023)

Mutagenicity and genotoxicity assessment of the emerging mycotoxin Versicolorin A, an Aflatoxin B1 precursor - Carine Al-Ayoubi; Maria Alonso-Jauregui; Amaya Azqueta; Julien Vignard; Gladys Mirey; Ophelie Rocher; Olivier Puel; Isabelle P. Oswald; Ariane Vettorazzi; Laura Soler (Environmental Pollution, 2023)

Blood biochemistry reference values for nesting Kemp's ridley turtles (Lepidochelys kempii) in Rancho Nuevo Sanctuary, Mexico - Valeria Leal-Sepúlveda; Miguel Angel Reyes-López; Fátima Yedith Camacho-Sánchez; Héctor Hugo Acosta-Sánchez; Kevin Alan Zavala-Félix; Catherine E. Hart; Alan A. Zavala-Norzagaray; Renato Leal-Moreno; Brenda Aracely Espinoza-Romo; A. Alonso Aguirre; Juan Carlos Sainz-Henández; César P. Ley-Quiñónez (Estuarine, Coastal and Shelf Science, 2023)

Mine water as a source of energy: an application in a coalfield in Laciana Valley (León, NW Spain) - A. Matas-Escamilla; R. Álvarez; F. García-Carro; L. Álvarez-Alonso; P. Cienfuegos; J. Menéndez; A. Ordóñez (Clean Technologies and Environmental Policy, 2023)
Mine water can be a renewable and economical source of geothermal and hydraulic energy. Nine discharges from closed and flooded coal mines in the Laciana Valley (León, NW Spain) have been studied. Various technologies for the energy use of mine water, as well as the influence of factors such as temperature, the need for water treatment, investment, potential customers and expansion capacity, have been evaluated by means of a decision-making tool. It is concluded that the most advantageous option is an open-loop geothermal system using the waters of a mountain mine, the temperature of which exceeds 14 °C and whose distance to customers is less than 2 km. A technical–economic viability study for a district heating network designed to supply heating and hot water to six public buildings in the nearby town of Villablino is presented. The proposed use of mine water might help areas that have been greatly affected socioeconomically by the closure of the mines and has other advantages compared to conventional energy systems, such as the reduction of CO 2 emissions. Graphical Abstract It showing the advantages of using mine water as an energy source for district heating and a simplified layout.

Wind and turbulence relationship with NO2 in an urban environment: a fine-scale observational analysis - C. Román-Cascón; C. Yagüe; P. Ortiz-Corral; E. Serrano; B. Sánchez; M. Sastre; G. Maqueda; E. Alonso-Blanco; B. Artiñano; F.J. Gómez-Moreno; E. Diaz-Ramiro; J. Fernández; et al. (Urban Climate, 2023)

Analysis of SAR-derived products to support emergency management during volcanic crisis: La Palma case study - P. Ezquerro; G. Bru; I. Galindo; O. Monserrat; J.C. García-Davalillo; N. Sánchez; I. Montoya; R. Palamà; R.M. Mateos; R. Pérez-López; E. González-Alonso; R. Grandin; et al. (Remote Sensing of Environment, 2023)

Fungal spore swelling and germination are restricted by the macrophage phagolysosome - María Fernanda Alonso; Judith M. Bain; Lars P. Erwig; Alistair J.P. Brown; Neil A.R. Gow (Fungal Biology, 2023)

Multiparametric analysis for the determination of radon potential areas in buildings on different soils of volcanic origin - C. Briones; J. Jubera; H. Alonso; J. Olaiz; J.T. Santana; N. Rodríguez-Brito; A.C. Arriola-Velásquez; N. Miquel; A. Tejera; P. Martel; E. González-Díaz; J.G. Rubiano (Science of The Total Environment, 2023)

Production of small peptides and low molecular weight amino acids by subcritical water from fish meal: Effect of pressurization agent - P. Barea; R. Melgosa; A.E. Illera; P. Alonso-Riaño; E. Díaz de Cerio; O. Benito-Román; Sagrario Beltrán; M. Teresa Sanz (Food Chemistry, 2023)

Airborne hyperspectral and Sentinel imagery to quantify winter wheat traits through ensemble modeling approaches - J. L. Pancorbo; M. Alonso-Ayuso; C. Camino; M. D. Raya-Sereno; P. J. Zarco-Tejada; I. Molina; J. L. Gabriel; M. Quemada (Precision Agriculture, 2023)
Early prediction of crop production by remote sensing (RS) may help to plan the harvest and ensure food security. This study aims to improve the quantification of yield, grain protein concentration (GPC), and nitrogen (N) output in winter wheat with RS imagery. Ground-truth wheat traits were measured at flowering and harvest in a field experiment combining four N and two water levels in central Spain over 2 years. Hyperspectral and thermal airborne images coincident with Sentinel-1 and Sentinel-2 were acquired at flowering. A parametric linear model using all hyperspectral normalized difference spectral indices (NDSI) and two non-parametric models (artificial neural network and random forest) were used to assess their estimation ability combining NDSIs and other RS indicators. The feasibility of using freely available multispectral satellite was tested by applying the same methodology but using Sentinel-1 and Sentinel-2 bands. Yield estimation obtained the highest R 2 value, showing that the visible and short-wave infrared region (VSWIR) had similar accuracy to the hyperspectral and Sentinel-2 imagery ( R 2 ≈ 0.84). The SWIR bands were important in the GPC estimation with both sensors, whereas N output was better estimated using red-edge-based NDSIs, obtaining satisfactory results with the hyperspectral sensor ( R 2 = 0.74) and with the Sentinel-2 ( R 2 = 0.62). When including the Sentinel-2 SWIR index, the NDSI (B11, B3) improved the estimation of N output ( R 2 = 0.71). Ensemble models based on Sentinel were found to be as reliable as those based on hyperspectral imagery, and including SWIR information improved the quantification of N-related traits.

Late stages of megagametophytogenesis: Archegonial development in Zamiaceae - M. Ydelia Sánchez-Tinoco; Dennis Wm. Stevenson; Andrew P. Vovides; Alejandro Alonso López; Lourdes G. Iglesias-Andreu; Edmundo García Moya; Galdy Hernández-Zárate (Flora, 2023)

FentonSims®: A novel interactive simulation tool for computational kinetics of microcontaminant removal by the solar photo-Fenton process - E. Gualda-Alonso; D. Rodríguez-García; P. Soriano-Molina; J.L. Guzmán; J.L. García Sánchez; J.L. Casas López; J.A. Sánchez Pérez (Chemical Engineering Journal, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Embryonic cerebrospinal fluid influence in the subependymal neurogenic niche in adult mouse hippocampus - M. Madrigal; P. Martín; F. Lamus; J.M. Fernandez; A. Gato; MI. Alonso (Tissue and Cell, 2023)

Comparison of Apgar score and neonatal parameters between ET and ICSI foals - Juliana S Fonte; Francieli P Carneiro; Barbara K Costa; Maria Augusta Alonso; Perla DC Fleury; Marc P Maserati; Claudia B Fernandes (Journal of Equine Veterinary Science, 2023)

Efficiency of equine oocyte recovery from post mortem ovaries or by ovum pick up - Catalina Castañeira; Ana P Flores Bragulat; Carolina N Alonso; Ayelen M Rodriguez; Guido A Rocchi; Jose M Zeledon (Journal of Equine Veterinary Science, 2023)

Radiomics analysis of bone marrow biopsy locations in [18F]FDG PET/CT images for measurable residual disease assessment in multiple myeloma - Eva Milara; Rafael Alonso; Lena Masseing; Alexander P. Seiffert; Adolfo Gómez-Grande; Enrique J. Gómez; Joaquín Martínez-López; Patricia Sánchez-González (Physical and Engineering Sciences in Medicine, 2023)
The combination of visual assessment of whole body [ 18 F]FDG PET images and evaluation of bone marrow samples by Multiparameter Flow Cytometry (MFC) or Next-Generation Sequencing (NGS) is currently the most common clinical practice for the detection of Measurable Residual Disease (MRD) in Multiple Myeloma (MM) patients. In this study, radiomic features extracted from the bone marrow biopsy locations are analyzed and compared to those extracted from the whole bone marrow in order to study the representativeness of these biopsy locations in the image-based MRD assessment. Whole body [ 18 F]FDG PET of 39 patients with newly diagnosed MM were included in the database, and visually evaluated by experts in nuclear medicine. A methodology for the segmentation of biopsy sites from PET images, including sternum and posterior iliac crest, and their subsequent quantification is proposed. First, starting from the bone marrow segmentation, a segmentation of the biopsy sites is performed. Then, segmentations are quantified extracting SUV metrics and radiomic features from the [ 18 F]FDG PET images and are evaluated by Mann–Whitney U-tests as valuable features differentiating PET+/PET− and MFC+ /MFC− groups. Moreover, correlation between whole bone marrow and biopsy sites is studied by Spearman ρ rank. Classification performance of the radiomics features is evaluated applying seven machine learning algorithms. Statistical analyses reveal that some images features are significant in PET+/PET− differentiation, such as SUV max , Gray Level Non-Uniformity or Entropy, especially with a balanced database where 16 of the features show a p value < 0.001. Correlation analyses between whole bone marrow and biopsy sites results in significant and acceptable coefficients, with 11 of the variables reaching a correlation coefficient greater than 0.7, with a maximum of 0.853. Machine learning algorithms demonstrate high performances in PET+/PET− classification reaching a maximum AUC of 0.974, but not for MFC+/MFC− classification. The results demonstrate the representativeness of sample sites as well as the effectiveness of extracted features (SUV metrics and radiomic features) from the [ 18 F]FDG PET images in MRD assessment in MM patients.

Canarian common ravens electrocution: a post-mortem case study - A. Fernandez; P. Diaz-Santana; M. Andrada; L. Marrero; P. Alonso; F. Consoli; J. Navarro; C. Fiorito; C. Díaz-Santana (Journal of Comparative Pathology, 2023)

Sensitivity of solar-induced fluorescence to spectral stray light in high resolution imaging spectroscopy - Loren P. Albert; K.C. Cushman; Yuqin Zong; David W. Allen; Luis Alonso; James R. Kellner (Remote Sensing of Environment, 2023)

Surfactant-enhanced mobilization of persistent organic pollutants: Potential for soil and sediment remediation and unintended consequences - Shiv Bolan; Lokesh P. Padhye; Catherine N. Mulligan; Emilio Ritore Alonso; Roger Saint-Fort; Tahereh Jasemizad; Chensi Wang; Tao Zhang; Jörg Rinklebe; Hailong Wang; Kadambot H.M. Siddique; M.B. Kirkham; et al. (Journal of Hazardous Materials, 2023)

Holistic methodology to reduce energy use and improve indoor air quality for demand-controlled ventilation - M. Justo Alonso; P. Liu; S.F. Marman; R.B. Jørgensen; H.M. Mathisen (Energy and Buildings, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Potential Distribution and Connectivity for Two Plethodontid Salamanders: Conservation Areas and Landscape Corridors for Two Endemic Species of México and Guatemala - René Bolom-Huet; Xareni P. Pacheco; Antonio Muñoz-Alonso; Armando Sunny (Environmental Management, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Spike architecture traits associated with type II resistance to fusarium head blight in bread wheat - M. F. Franco; G. A. Lori; G. Cendoya; M. P. Alonso; J. S. Panelo; I. Malbrán; N. E. Mirabella; A. C. Pontaroli (Euphytica, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genomic insights into an andean multiresistant soil actinobacterium of biotechnological interest - Daniel Gonzalo Alonso-Reyes; Fátima Silvina Galván; Luciano Raúl Portero; Natalia Noelia Alvarado; María Eugenia Farías; Martín P. Vazquez; Virginia Helena Albarracín (World Journal of Microbiology and Biotechnology, 2021)

High versus standard doses of corticosteroids in severe COVID-19: a retrospective cohort study - Enric Monreal; Susana Sainz de la Maza; Elena Natera-Villalba; Álvaro Beltrán-Corbellini; Fernando Rodríguez-Jorge; Jose Ignacio Fernández-Velasco; Paulette Walo-Delgado; Alfonso Muriel; Javier Zamora; Araceli Alonso-Canovas; Jesús Fortún; Luis Manzano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Computer-aided diagnosis based on hand thermal, RGB images, and grip force using artificial intelligence as screening tool for rheumatoid arthritis in women - Antonio Alarcón-Paredes; Iris P. Guzmán-Guzmán; Diana E. Hernández-Rosales; José E. Navarro-Zarza; Jessica Cantillo-Negrete; René E. Cuevas-Valencia; Gustavo A. Alonso (Medical & Biological Engineering & Computing, 2021)

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

Effects of leaf litter extracts from four tree species on aquatic invertebrates: an ecotoxicological risk assessment approach - A. Alonso; B. R. Vázquez de Aldana; P. Castro-Díez; S. Medina-Villar; M. E. Pérez-Corona (Aquatic Ecology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Pseudonocardia filamentous bulking sludge in an industrial wastewater treatment plant as revealed by Illumina amplicon sequencing - J. L. Alonso; A. Soler; L. Moreno-Mesonero; E. Rodríguez; P. Infante (International Journal of Environmental Science and Technology, 2020)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Effect of the mother tree age and acorn weight in the regenerative characteristics of Quercus faginea - I. M. Alonso-Crespo; F. Silla; P. Jiménez del Nogal; M. J. Fernández; C. Martínez-Ruiz; B. Fernández-Santos (European Journal of Forest Research, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system - Pascal Alonso; Laurence Blondin; Pierre Gladieux; Frédéric Mahé; Hervé Sanguin; Romain Ferdinand; Denis Filloux; Eric Desmarais; Frédérique Cerqueira; Baihui Jin; Huichuan Huang; Xiahong He; et al. (Environmental Microbiology, 2020)
Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.

Using MaxEnt algorithm to assess habitat suitability of a potential Iberian lynx population in central Iberian Peninsula - P. Alfaya; J. G. Casanovas; J. Lobón-Rovira; B. Matallanas; A. Cruz; P. Arana; G. Alonso (Community Ecology, 2019)

Early Diagnosis of Vegetation Health From High-Resolution Hyperspectral and Thermal Imagery: Lessons Learned From Empirical Relationships and Radiative Transfer Modelling - R. Hernández-Clemente; A. Hornero; M. Mottus; J. Penuelas; V. González-Dugo; J. C. Jiménez; L. Suárez; L. Alonso; P. J. Zarco-Tejada (Current Forestry Reports, 2019)

Coseismic landslides triggered by the 2018 Hokkaido, Japan (Mw 6.6), earthquake: spatial distribution, controlling factors, and possible failure mechanism - Fengrui Wang; Xuanmei Fan; Ali P. Yunus; Srikrishnan Siva Subramanian; Andres Alonso-Rodriguez; Lanxin Dai; Qiang Xu; Runqiu Huang (Landslides, 2019)

Facies and sequence analysis of Miocene open-shelf warm-temperate carbonates in Portimão (Lagos-Portimão Formation, Portugal) - I. Armenteros; C. J. Dabrio; P. Legoinha; J. A. González-Delgado; A. Martínez-Graña; G. Alonso-Gavilán; J. Civis; J. Pais (Facies, 2019)

Passive sampling as a feasible tool for mapping and model evaluation of the spatial distribution of nitrogen oxides in the city of Curitiba, Brazil - Erika Felix; Lars Gidhagen; Marcelo F. Alonso; Everaldo P. Nahirny; Bruno L. Alves; David Segersson; Jorge H. Amorim (Air Quality, Atmosphere & Health, 2019)

Empirical selection between least‐cost and current‐flow designs for establishing wildlife corridors in Gabon - Hadrien P. A. Vanthomme; Brave S. Nzamba; Alfonso Alonso; Angelique F. Todd (Conservation Biology, 2019)
Corridors are intended to increase species survival by abating landscape fragmentation resulting from the conversion of natural habitats into human‐dominated matrices. Conservation scientists often rely on 1 type of corridor model, typically the least‐cost model or current‐flow model, to construct a linkage design, and their choice is not usually based on theory or empirical evidence. We developed a method to empirically confirm whether corridors produced by these 2 models are used by target species under current landscape conditions. We applied this method in the Gamba landscape between 2 national parks in southwestern Gabon. We collected signs of presence of African forest elephant ( Loxodonta cyclotis ), forest buffalo ( Syncerus caffer nanus ), and 2 apes, western lowland gorilla ( Gorilla gorilla gorilla ) and central chimpanzee ( Pan troglodytes troglodytes ), on transects. We used patch‐occupancy models to identify least‐cost and current‐flow corridors for these 4 species. On average, 28.7% of current‐flow corridors overlapped with least‐cost corridors, confirming that the choice of corridor model can affect the location of the resulting linkage design. We validated these corridors by monitoring signs and examining camera detections on new transects within and outside modeled corridors. Current‐flow corridors performed better than least‐cost corridors for elephants, whereas the opposite was found for buffalo and apes. Locations of the highest priority corridors for the 3 taxa did not overlap, and only 18.3% of their combined surface was common among 2 species. We used centrality metrics to calculate the average contribution of corridor pixels to landscape connectivity and derived an index that can be used to prioritize corridors. As a result, we recommend protecting at least 17.4% of the land surface area around Gamba town to preserve the preferred travel routes of the target species.

Air and wet bulb temperature lapse rates and their impact on snowmaking in a Pyrenean ski resort - Juan Ignacio López-Moreno; F. Navarro-Serrano; C. Azorín-Molina; P. Sánchez-Navarrete; E. Alonso-González; I. Rico; E. Morán-Tejeda; S. Buisan; J. Revuelto; M. Pons; S.M. Vicente-Serrano (Theoretical and Applied Climatology, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Analysis of pig trading networks and practices in Uganda - C. Atherstone; R. G. Galiwango; D. Grace; S. Alonso; N. K. Dhand; M. P. Ward; S. M. Mor (Tropical Animal Health and Production, 2019)

The Effects of Area and Habitat Heterogeneity on Bird Richness and Composition in High Elevation Wetlands (“Bofedales”) of the Central Andes of Peru - Grace P. Servat; Renzo Alcocer; Melvi V. Larico; Magaly E. Olarte; Reynaldo Linares-Palomino; Alfonso Alonso; Karim Ledesma (Wetlands, 2018)

Mannheimia haemolytica OmpP2-like is an amyloid-like protein, forms filaments, takes part in cell adhesion and is part of biofilms - J. F. Montes García; Sergio Vaca; Norma L. Delgado; Alina Uribe-García; Candelario Vázquez; P. Sánchez Alonso; J. Xicohtencatl Cortes; A. Cruz Cordoba; E. Negrete Abascal (Antonie van Leeuwenhoek, 2018)

Betanodavirus infection in bath‐challenged Solea senegalensis juveniles: A comparative analysis of RGNNV , SJNNV and reassortant strains - Sandra Souto; José G. Olveira; M. Carmen Alonso; Carlos P. Dopazo; Isabel Bandín (Journal of Fish Diseases, 2018)
Senegalese sole has been shown to be highly susceptible to betanodavirus infection, although virulence differences were observed between strains. To study the mechanisms involved in these differences, we have analysed the replication in brain tissue of three strains with different genotypes during 15 days after bath infection. In addition, possible portals of entry for betanodavirus into sole were investigated. The reassortant RGNNV / SJNNV and the SJNNV strain reached the brain after 1 and 2 days postinfection, respectively. Although no RGNNV replication was detected until day 3–4 postinfection, at the end of the experiment this strain yielded the highest viral load; this is in accordance with previous studies in which sole infected with the reassortant showed more acute signs and earlier mortality than the RGNNV and SJNNV strains. Differences between strains were also observed in the possible portals of entry. Thus, whereas the reassortant strain could infect sole mainly through the skin or the oral route, and, to a minor extent, through the gills, the SJNNV strain seems to enter fish only through the gills and the RGNNV strain could use all tissues indistinctly. Taken together, all these results support the hypothesis that reassortment has improved betanodavirus infectivity for sole.

Selection for high spike fertility index increases genetic progress in grain yield and stability in bread wheat - M. P. Alonso; N. E. Mirabella; J. S. Panelo; M. G. Cendoya; A. C. Pontaroli (Euphytica, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Summer-autumn air pollution in León, Spain: changes in aerosol size distribution and expected effects on the respiratory tract - F. Oduber; A. Castro; A.I. Calvo; C. Blanco-Alegre; E. Alonso-Blanco; P. Belmonte; R. Fraile (Air Quality, Atmosphere & Health, 2018)

A new contribution to our knowledge of the large-bodied theropods from the Barremian of the Iberian Peninsula: the “Barranco del Hocino” site (Spain) - A. Alonso; J. M. Gasca; P. Navarro-Lorbés; C. Rubio; J. I. Canudo (Journal of Iberian Geology, 2018)

Explanatory Power of Human and Environmental Pressures on the Fish Community of the Grand Bank before and after the Biomass Collapse - Danielle P. Dempsey; Wendy C. Gentleman; Pierre Pepin; Mariano Koen-Alonso (Frontiers in Marine Science, 2018)

Ecological plant epigenetics: Evidence from model and non‐model species, and the way forward - Christina L. Richards; Conchita Alonso; Claude Becker; Oliver Bossdorf; Etienne Bucher; Maria Colomé‐Tatché; Walter Durka; Jan Engelhardt; Bence Gaspar; Andreas Gogol‐Döring; Ivo Grosse; Thomas P. van Gurp; et al. (Ecology Letters, 2017)
Growing evidence shows that epigenetic mechanisms contribute to complex traits, with implications across many fields of biology. In plant ecology, recent studies have attempted to merge ecological experiments with epigenetic analyses to elucidate the contribution of epigenetics to plant phenotypes, stress responses, adaptation to habitat, and range distributions. While there has been some progress in revealing the role of epigenetics in ecological processes, studies with non‐model species have so far been limited to describing broad patterns based on anonymous markers of DNA methylation. In contrast, studies with model species have benefited from powerful genomic resources , which contribute to a more mechanistic understanding but have limited ecological realism. Understanding the significance of epigenetics for plant ecology requires increased transfer of knowledge and methods from model species research to genomes of evolutionarily divergent species, and examination of responses to complex natural environments at a more mechanistic level. This requires transforming genomics tools specifically for studying non‐model species, which is challenging given the large and often polyploid genomes of plants. Collaboration among molecular geneticists, ecologists and bioinformaticians promises to enhance our understanding of the mutual links between genome function and ecological processes.

Evaluation of the Protective Effects of Sarains on H2O2-Induced Mitochondrial Dysfunction and Oxidative Stress in SH-SY5Y Neuroblastoma Cells - Rebeca Alvariño; Eva Alonso; Marie-Aude Tribalat; Sandra Gegunde; Olivier P. Thomas; Luis M. Botana (Neurotoxicity Research, 2017)

In vivo study of viral haemorrhagic septicaemia virus and infectious pancreatic necrosis virus coexistence in Senegalese sole ( Solea senegalensis ) - C López‐Vázquez; M C Alonso; C P Dopazo; I Bandín (Journal of Fish Diseases, 2017)
The effect of IPNV ‐ VHSV coinfection and superinfection on the mortality caused by both viruses in Senegalese sole has been analysed. No effect was observed after coinfection. However, a clear viral interference was recorded between a primary IPNV and a subsequent VHSV infection, which led to a survival increase in the infected sole of 50% points when compared with fish infected only with VHSV . The significantly higher Mx transcriptional values in the fish pre‐exposed to IPNV (at least at first days after superinfection) and the increased daily mortality when low Mx transcriptional levels were recorded suggest that Mx may be involved in the protective effect against VHSV infection. However, in fish subjected to VHSV primary/ IPNV secondary infection, no interference was observed.

Morphological and functional aspects of the epidermis of the sea lamprey Petromyzon marinus throughout development - R. Rodríguez‐Alonso; M. Megías; M. A. Pombal; P. Molist (Journal of Fish Biology, 2017)
The development of the epidermis of sea lamprey Petromyzon marinus along the whole life cycle was studied using conventional staining techniques and lectin histochemistry. The epidermis undergoes variations in morphology and thickness throughout development. The simple cuboidal epithelium found in the epidermis of prolarvae becomes stratified cubic in the adult by increasing the number of cell layers. The cuticle thickness undergoes a steady increase during the larval period. There are changes in the glycoconjugate composition of the three main cell types of the P. marinus epidermis, mucous, granular and skein cells, which are more pronounced after metamorphosis. The Alcian blue–periodic acid Schiff ( AB–PAS ) histochemical method shows the presence of both acidic and neutral glycoconjugates in the mucous cells, indicating their secretory function. Moreover, lectin analysis reveals a mucous secretion containing glycoconjugates such as sulphated glycosaminoglycans ( N ‐acetylglucosamine and N ‐acetylgalactosamine) and N ‐glycoproteins rich in mannose. Although granular cells are AB–PAS negative, they exhibit a similar glycoconjugate composition to the mucous cells. Moreover, granular cells show sialic acid positivity in larvae but this monosaccharide residue is not detected after metamorphosis. The skein cells, a unique cell of lampreys, are negative to AB–PAS staining but they mostly contain l ‐fucose and sialic acid residues, which also disappear after metamorphosis. The function of the granular and skein cells is still unknown but the role of their glycoconjugate composition is discussed. In addition, a different cellular origin is suggested for these two types of cells.

Isolated theropod teeth associated with sauropod remains from El Oterillo II (Early Cretaceous) site of Salas de los Infantes (Burgos, Spain) - A. Alonso; J. I. Canudo; F. Torcida Fernández-Baldor; P. Huerta (Journal of Iberian Geology, 2017)

Modelling and management options for salmonid sport fisheries: A case study from Patagonia, Argentina - M. Rechencq; P. H. Vigliano; G. E. Lippolt; M. F. Alonso; P. J. Macchi; P. A. Alvear; V. Hougham; M. A. Denegri; G. Blasetti; R. Juncos; M. V. Fernandez; M. E. Lallement; et al. (Fisheries Management and Ecology, 2017)
Salmonid sport fishery management in Argentinian Patagonia is usually guided by stakeholder perceptions, which do not consider the biological and ecological constraints acting upon aquatic resources. An example of this are management policies for Traful Lake, where Atlantic salmon, Salmo salar L., was actively stocked during the last decade in an attempt to change the fish assemblage structure and to create a highly valuable sport fishery. This study assesses the likelihood of these policies achieving such assemblage structure changes through the study of affluent‐stream suitability as spawning and breeding grounds, lake fish assemblage parameters, trophic diversity and possible competition due to diet overlap. This study also assesses alternative management practices through population simulations and bioenergetic modelling under diverse catch‐size limit scenarios. This study concludes that it is not advisable to try to generate a unique and distinctive sport fishery by stocking Atlantic salmon in an already renowned fishery in Northern Patagonia. Instead, a more comprehensive framework for decision‐making is suggested, involving short‐term studies that go beyond the specific problem of the target species and incorporate the whole fish assemblage using diverse approaches and modelling strategies.

Augmented Reality in a Hiking Tour of the Miocene Geoheritage of the Central Algarve Cliffs (Portugal) - A. M. Martínez-Graña; P. Legoinha; J. A. González-Delgado; C. J. Dabrio; J. Pais; J. L. Goy; C. Zazo; J. Civis; I. Armenteros; G. Alonso-Gavilan; R. Dias; T. Cunha (Geoheritage, 2017)

The genotypic study of Mycobacterium tuberculosis complex resistant to isoniazid: Galicia, Spain (2008–2013) - M. L. Pérez del Molino; G. Barbeito-Castiñeiras; B. Mejuto; P. Alonso; A. Fernández; G. González-Mediero (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Analytical Method for Biomonitoring of PAH Using Leaves of Bitter Orange Trees (Citrus aurantium): a Case Study in South Spain - D. Fasani; P. Fermo; P. J. Barroso; J. Martín; J. L. Santos; I. Aparicio; E. Alonso (Water, Air, & Soil Pollution, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Effects of an environmentally relevant concentration of diuron on oyster genitors during gametogenesis: responses of early molecular and cellular markers and physiological impacts - F. Akcha; A. Barranger; E. Bachère; C. Heude Berthelin; D. Piquemal; P. Alonso; R. Rondon Sallan; G. Dimastrogiovanni; C. Porte; D. Menard; A. Szczybelski; A. Benabdelmouna; et al. (Environmental Science and Pollution Research, 2016)

First record of the genus Jenynsia from marine water on the coast of Punta del Este, Maldonado, Uruguay (Cyprinodontiformes: Anablepidae) - P. Calviño; F. Alonso (Journal of Fish Biology, 2016)
The first report of the genus Jenynsia occurring in marine waters is presented here. The evolution of high salinity tolerance within Anablepidae is discussed and a hypothesis is proposed that this characteristic is a plesiomorphic trait in Jenynsia which was probably present in the common ancestor of the Anablepidae.

Effect of Zinc Intake on Growth in Infants: A Meta-analysis - M. Nissensohn; A. Sánchez-Villegas; D. Fuentes Lugo; P. Henríquez Sánchez; J. Doreste Alonso; L. Peña Quintana; C. Ruano; N. L. Lowe; V. Hall Moran; A. L. Skinner; M. Warthon-Medina; L. Serra-Majem (Critical Reviews in Food Science and Nutrition, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Do the invasive trees, Ailanthus altissima and Robinia pseudoacacia, alter litterfall dynamics and soil properties of riparian ecosystems in Central Spain? - S. Medina-Villar; P. Castro-Díez; A. Alonso; I. Cabra-Rivas; I. M. Parker; E. Pérez-Corona (Plant and Soil, 2015)

Differences between endocarditis caused by Streptococcus bovis and Enterococcus spp. and their association with colorectal cancer - J. Corredoira; M. J. García-País; A. Coira; R. Rabuñal; F. García-Garrote; J. Pita; A. Rodríguez-Macías; M. Blanco; L. Lopez-Roses; M.J. López-Álvarez; M. P. Alonso-García (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

ASIC2 is present in human mechanosensory neurons of the dorsal root ganglia and in mechanoreceptors of the glabrous skin - R. Cabo; P. Alonso; E. Viña; G. Vázquez; A. Gago; J. Feito; F. J. Pérez-Moltó; O. García-Suárez; J. A. Vega (Histochemistry and Cell Biology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Ichthyofauna of the Selvagens Islands. Do small coastal areas show high species richness in the northeastern Atlantic? - Frederico Almada; David Abecasis; David Villegas-Ríos; Sofia Henriques; Miguel P. Pais; Marisa Batista; Bárbara Horta e Costa; Joana Martins; Inês Tojeira; Nuno Vasco Rodrigues; Ricardo Araújo; Miguel Souto; et al. (Marine Biology Research, 2015)

Analysis and detection of functional outliers in water quality parameters from different automated monitoring stations in the Nalón River Basin (Northern Spain) - J. I. Piñeiro Di Blasi; J. Martínez Torres; P. J. García Nieto; J. R. Alonso Fernández; C. Díaz Muñiz; J. Taboada (Environmental Science and Pollution Research, 2015)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

An holistic ecological analysis of the diet of Cory's shearwaters using prey morphological characters and DNA barcoding - Hany Alonso; José P. Granadeiro; Silke Waap; José Xavier; William O. C. Symondson; Jaime A. Ramos; Paulo Catry (Molecular Ecology, 2014)
Knowledge of the dietary choices and trophic niches of organisms is the key to understanding their roles in ecosystems. In seabird diet studies, prey identification is a difficult challenge, often yielding results with technique‐specific biases. Additionally, sampling efforts are often not extensive enough to reveal intrapopulational variation. Immature animals, which may constitute up to 50% of a population, may occupy a significantly different trophic niche to more experienced birds, but this remains largely unexplored. We investigated the diet of Cory's shearwater ( Calonectris diomedea ) from Selvagem Grande, an island located off the northwest African coast, collecting a total of 698 regurgitate samples over three consecutive breeding seasons. The diet was assessed using two complementary approaches for prey identification: conventional morphological analysis (using fish vertebrae, otoliths and cephalopod beaks) and DNA barcoding of the 16S r RNA mitochondrial gene, in cases where a positive identification could not be retrieved. Species assignments employed BLAST and distance‐based methods, as well as direct optimization of the tree length based on unaligned sequences in POY . This method resulted in robust tree estimates and species assignments, showing its potential for DNA barcoding of stomach contents using hypervariable markers such as the 16S. The molecular approach increased taxonomic resolution and revealed an additional 17 taxa. Diet differed significantly according to breeding status, sex, breeding phase (prelaying and chick rearing) and year. Such direct evidence of trophic segregation within the same population has rarely been shown in seabirds and highlights the importance of including such variables in ecosystem‐based management approaches.

Immunohistochemical markers of distant metastasis in laryngeal and hypopharyngeal squamous cell carcinomas - Juan P. Rodrigo; Patricia Martínez; Eva Allonca; Laura Alonso-Durán; Carlos Suárez; Aurora Astudillo; Juana María García-Pedrero (Clinical & Experimental Metastasis, 2014)

Is colonoscopy necessary in cases of infection by Streptococcus bovis biotype II? - J. C. Corredoira; M. P. Alonso; M. J. García-País; R. Rabuñal; F. García-Garrote; L. López-Roses; A. Lancho; A. Coira; J. Pita; D. Velasco; M. J. López-Álvarez; H. Tjalsma; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Using Genetic Profiles of African Forest Elephants to Infer Population Structure, Movements, and Habitat Use in a Conservation and Development Landscape in Gabon - L. S. EGGERT; R. BUIJ; M. E. LEE; P. CAMPBELL; F. DALLMEIER; R. C. FLEISCHER; A. ALONSO; J. E. MALDONADO (Conservation Biology, 2014)
Conservation of wide‐ranging species, such as the African forest elephant ( Loxodonta cyclotis ), depends on fully protected areas and multiple‐use areas (MUA) that provide habitat connectivity. In the Gamba Complex of Protected Areas in Gabon, which includes 2 national parks separated by a MUA containing energy and forestry concessions, we studied forest elephants to evaluate the importance of the MUA to wide‐ranging species. We extracted DNA from elephant dung samples and used genetic information to identify over 500 individuals in the MUA and the parks. We then examined patterns of nuclear microsatellites and mitochondrial control‐region sequences to infer population structure, movement patterns, and habitat use by age and sex. Population structure was weak but significant, and differentiation was more pronounced during the wet season. Within the MUA, males were more strongly associated with open habitats, such as wetlands and savannas, than females during the dry season. Many of the movements detected within and between seasons involved the wetlands and bordering lagoons. Our results suggest that the MUA provides year‐round habitat for some elephants and additional habitat for others whose primary range is in the parks. With the continuing loss of roadless wilderness areas in Central Africa, well‐managed MUAs will likely be important to the conservation of wide‐ranging species. Utilización de Perfiles Genéticos de Elefantes Africanos para Inferir su Estructura Poblacional, Movimientos y Uso del Hábitat en un Paisaje con Conservación y Desarrollo en Gabón Resumenfgs

Polyphenols and the Modulation of Gene Expression Pathways: Can We Eat Our Way Out of the Danger of Chronic Disease? - Jorge Joven; Vicente Micol; Antonio Segura-Carretero; Carlos Alonso-Villaverde; Javier A. Menéndez; for the Bioactive Food Components P (Critical Reviews in Food Science and Nutrition, 2014)

Turbidity Prediction in a River Basin by Using Artificial Neural Networks: A Case Study in Northern Spain - C. Iglesias; J. Martínez Torres; P. J. García Nieto; J. R. Alonso Fernández; C. Díaz Muñiz; J. I. Piñeiro; J. Taboada (Water Resources Management, 2014)

Cd-induced phytochelatin synthesis in Dittrichia viscosa (L.) Greuter is determined by the dilution of the culture medium - R. Fernández; D. Fernández-Fuego; P. Rodríguez-González; J. I. García Alonso; A. Bertrand; A. González (Environmental Science and Pollution Research, 2014)

What explains variation in the impacts of exotic plant invasions on the nitrogen cycle? A meta‐analysis - P. Castro‐Díez; O. Godoy; A. Alonso; A. Gallardo; A. Saldaña (Ecology Letters, 2014)
Exotic plant invasions can notably alter the nitrogen (N) cycle of ecosystems. However, there is large variation in the magnitude and direction of their impact that remains unexplained. We present a structured meta‐analysis of 100 papers, covering 113 invasive plant species with 345 cases of invasion across the globe and reporting impacts on N cycle‐related metrics. We aim to explain heterogeneity of impacts by considering methodological aspects, properties of the invaded site and phylogenetic and functional characteristics of the invaders and the natives. Overall, plant invasions increased N pools and accelerated fluxes, even when excluding N‐fixing invaders. The impact on N pools depended mainly on functional differences and was greater when the invasive plants and the natives differed in N‐fixation ability, plant height and plant/leaf habit. Furthermore, the impact on N fluxes was related mainly to climate, being greater under warm and moist conditions. Our findings show that more functionally distant invaders occurring in mild climates are causing the strongest alterations to the N cycle.

Support Vector Machines and Multilayer Perceptron Networks Used to Evaluate the Cyanotoxins Presence from Experimental Cyanobacteria Concentrations in the Trasona Reservoir (Northern Spain) - J. A. Vilán Vilán; J. R. Alonso Fernández; P. J. García Nieto; F. Sánchez Lasheras; F. J. de Cos Juez; C. Díaz Muñiz (Water Resources Management, 2013)

Use the backbone of your samples: fish vertebrae reduces biases associated with otoliths in seabird diet studies - Hany Alonso; José P. Granadeiro; Jaime A. Ramos; Paulo Catry (Journal of Ornithology, 2013)

Bimodality in stable isotope composition facilitates the tracing of carbon transfer from macrophytes to higher trophic levels - Raquel Mendonça; Sarian Kosten; Gissell Lacerot; Néstor Mazzeo; Fábio Roland; Jean P. Ometto; Eduardo Alonso Paz; Claudia Petean Bove; Norma Catarina Bueno; José Henrique C. Gomes; Marten Scheffer (Hydrobiologia, 2013)

Climate change and infectious diseases: Can we meet the needs for better prediction? - Xavier Rodó; Mercedes Pascual; Francisco J. Doblas-Reyes; Alexander Gershunov; Dáithí A. Stone; Filippo Giorgi; Peter J. Hudson; James Kinter; Miquel-Àngel Rodríguez-Arias; Nils Ch. Stenseth; David Alonso; Javier García-Serrano; et al. (Climatic Change, 2013)

Study of the impact of wildfire emissions, through MOPITT total CO column, at different spatial scales - A. Calle; P. Salvador; F. González-Alonso (International Journal of Remote Sensing, 2013)

Structural covariance of the neostriatum with regional gray matter volumes - C. Soriano-Mas; B. J. Harrison; J. Pujol; M. López-Solà; R. Hernández-Ribas; P. Alonso; O. Contreras-Rodríguez; M. Giménez; L. Blanco-Hinojo; H. Ortiz; J. Deus; J. M. Menchón; et al. (Brain Structure and Function, 2013)

Combining linkage and association mapping to search for markers linked to the flat fruit character in peach - R. Picañol; I. Eduardo; M. J. Aranzana; W. Howad; I. Batlle; I. Iglesias; J. M. Alonso; P. Arús (Euphytica, 2013)

Time-dependent changes in glucose and insulin regulation during intermittent hypoxia and continuous hypoxia - Euhan J. Lee; Laura C. Alonso; Darko Stefanovski; Hilary C. Strollo; Lia C. Romano; Baobo Zou; Srikanth Singamsetty; Keith A. Yester; Kenneth R. McGaffin; Adolfo Garcia-Ocana; Christopher P. O’Donnell (European Journal of Applied Physiology, 2013)

Could research in the native range, and non-target host range in Australia, have helped predict host range of the parasitoid Microctonus aethiopoides Loan (Hymenoptera: Braconidae), a biological control agent introduced for Sitona discoideus Gyllenhal (Coleoptera: Curculionidae) in New Zealand? - B. I. P. Barratt; R. G. Oberprieler; D. M. Barton; M. Mouna; M. Stevens; M. A. Alonso-Zarazaga; C. J. Vink; C. M. Ferguson (BioControl, 2012)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Rainfall-Driven Amplification of Seasonal Acidification in Poorly Buffered Tropical Streams - Gaston E. Small; Marcelo Ardón; Alan P. Jackman; John H. Duff; Frank J. Triska; Alonso Ramírez; Marcía Snyder; Catherine M. Pringle (Ecosystems, 2012)

Deep EST profiling of developing fenugreek endosperm to investigate galactomannan biosynthesis and its regulation - Yan Wang; Ana P. Alonso; Curtis G. Wilkerson; Kenneth Keegstra (Plant Molecular Biology, 2012)

Parent–offspring dietary segregation of Cory’s shearwaters breeding in contrasting environments - Hany Alonso; José P. Granadeiro; Vitor H. Paiva; Ana S. Dias; Jaime A. Ramos; Paulo Catry (Marine Biology, 2012)

Genetic polymorphisms among C57BL/6 mouse inbred strains - Esther Zurita; Mónica Chagoyen; Marta Cantero; Rosario Alonso; Anna González-Neira; Alejandro López-Jiménez; José Antonio López-Moreno; Carlisle P. Landel; Javier Benítez; Florencio Pazos; Lluís Montoliu (Transgenic Research, 2011)

Association between multiple sclerosis and Candida species: evidence from a case-control study - J. Benito-León; D. Pisa; R. Alonso; P. Calleja; M. Díaz-Sánchez; L. Carrasco (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Cortical processing of facial tactile stimuli in temporomandibular disorder as revealed by magnetoencephalography - Aurelio A. Alonso; Ioannis G. Koutlas; Arthur C. Leuthold; Scott M. Lewis; Apostolos P. Georgopoulos (Experimental Brain Research, 2010)

Scale-dependent effects of pines on the herbaceous layer diversity in a semi-arid mediterranean ecosystem - J. Madrigal-González; J. García-Rodríguez; A. Puerto-Martín; B. Fernández-Santos; P. Alonso-Rojo (Community Ecology, 2010)

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Effects of exotic invasive trees on nitrogen cycling: a case study in Central Spain - P. Castro-Díez; N. González-Muñoz; A. Alonso; A. Gallardo; L. Poorter (Biological Invasions, 2009)

Taking species abundance distributions beyond individuals - Hélène Morlon; Ethan P. White; Rampal S. Etienne; Jessica L. Green; Annette Ostling; David Alonso; Brian J. Enquist; Fangliang He; Allen Hurlbert; Anne E. Magurran; Brian A. Maurer; Brian J. McGill; et al. (Ecology Letters, 2009)
The species abundance distribution (SAD) is one of the few universal patterns in ecology. Research on this fundamental distribution has primarily focused on the study of numerical counts, irrespective of the traits of individuals. Here we show that considering a set of Generalized Species Abundance Distributions (GSADs) encompassing several abundance measures, such as numerical abundance, biomass and resource use, can provide novel insights into the structure of ecological communities and the forces that organize them. We use a taxonomically diverse combination of macroecological data sets to investigate the similarities and differences between GSADs. We then use probability theory to explore, under parsimonious assumptions, theoretical linkages among them. Our study suggests that examining different GSADs simultaneously in natural systems may help with assessing determinants of community structure. Broadening SADs to encompass multiple abundance measures opens novel perspectives in biodiversity research and warrants future empirical and theoretical developments.

Coinfection is an important factor in epidemiological studies: the first serosurvey of the aoudad (Ammotragus lervia) - M. G. Candela; E. Serrano; C. Martinez-Carrasco; P. Martín-Atance; M. J. Cubero; F. Alonso; L. Leon (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Application of in situ detection techniques to determine the systemic condition of lymphocystis disease virus infection in cultured gilt‐head seabream, Sparus aurata L. - I Cano; P Ferro; M C Alonso; C Sarasquete; E Garcia‐Rosado; J J Borrego; D Castro (Journal of Fish Diseases, 2009)
Immunohistochemistry (IHC) and in situ hybridization (ISH) techniques have been used for the detection of lymphocystis disease virus (LCDV) in formalin‐fixed, paraffin‐embedded tissues from gilt‐head seabream, Sparus aurata L. Diseased and recovered fish from the same population were analysed. IHC was performed with a polyclonal antibody against a 60‐kDa viral protein. A specific digoxigenin‐labelled probe, obtained by PCR amplification of a 270‐bp fragment of the gene coding the LCDV major capsid protein, was used for ISH. LCDV was detected in skin dermis and gill lamellae, as well as in several internal organs such as the intestine, liver, spleen and kidney using both techniques. Fibroblasts, hepatocytes and macrophages seem to be target cells for virus replication. The presence of lymphocystis cells in the dermis of the skin and caudal fin, and necrotic changes in the epithelium of proximal renal tubules were the only histological alterations observed in fish showing signs of the disease.

What explains the invading success of the aquatic mud snail Potamopyrgus antipodarum (Hydrobiidae, Mollusca)? - A. Alonso; P. Castro-Díez (Hydrobiologia, 2008)

Decline in the workload associated with the serodiagnosis of syphilis in a general hospital: 1994–2004 - A. Burillo; C. Fernández-Pérez; M. Rivera; R. Alonso; P. Catalán; E. Bouza (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Cortical processing of tactile stimuli applied in quick succession across the fingertips: temporal evolution of dipole sources revealed by magnetoencephalography - Elissaios Karageorgiou; Ioannis G. Koutlas; Aurelio A. Alonso; Arthur C. Leuthold; Scott M. Lewis; Apostolos P. Georgopoulos (Experimental Brain Research, 2008)

Directed Aerial Descent Behavior in African Canopy Ants (Hymenoptera: Formicidae) - S. P. Yanoviak; B. L. Fisher; A. Alonso (Journal of Insect Behavior, 2008)

Characteristics of Streptococcus bovis endocarditis and its differences with Streptococcus viridans endocarditis - J. Corredoira; M. P. Alonso; A. Coira; E. Casariego; C. Arias; D. Alonso; J. Pita; A. Rodriguez; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Electrophysiological Modeling of Fibroblasts and their Interaction with Myocytes - Frank B. Sachse; Alonso P. Moreno; J. A. Abildskov (Annals of Biomedical Engineering, 2008)

Insect Resistance Monitoring for Bt Maize Cultivation in the EU: Proposal from the Industry IRM Working Group - E. Alacalde; F. Amijee; G. Blache; C. Bremer; S. Fernandez; M. Garcia-Alonso; K. Holt; G. Legris; C. Novillo; P. Schlotter; N. Storer; B. Tinland (Journal of Consumer Protection and Food Safety, 2007)

Species abundance distributions: moving beyond single prediction theories to integration within an ecological framework - Brian J. McGill; Rampal S. Etienne; John S. Gray; David Alonso; Marti J. Anderson; Habtamu Kassa Benecha; Maria Dornelas; Brian J. Enquist; Jessica L. Green; Fangliang He; Allen H. Hurlbert; Anne E. Magurran; et al. (Ecology Letters, 2007)
Species abundance distributions (SADs) follow one of ecology’s oldest and most universal laws – every community shows a hollow curve or hyperbolic shape on a histogram with many rare species and just a few common species. Here, we review theoretical, empirical and statistical developments in the study of SADs. Several key points emerge. (i) Literally dozens of models have been proposed to explain the hollow curve. Unfortunately, very few models are ever rejected, primarily because few theories make any predictions beyond the hollow‐curve SAD itself. (ii) Interesting work has been performed both empirically and theoretically, which goes beyond the hollow‐curve prediction to provide a rich variety of information about how SADs behave. These include the study of SADs along environmental gradients and theories that integrate SADs with other biodiversity patterns. Central to this body of work is an effort to move beyond treating the SAD in isolation and to integrate the SAD into its ecological context to enable making many predictions. (iii) Moving forward will entail understanding how sampling and scale affect SADs and developing statistical tools for describing and comparing SADs. We are optimistic that SADs can provide significant insights into basic and applied ecological science.

Increase in XET activity in bean (Phaseolus vulgaris L.) cells habituated to dichlobenil - A. Alonso-Simón; P. García-Angulo; A. E. Encina; J. M. Álvarez; J. L. Acebes; T. Hayashi (Planta, 2007)

On the effect of subinertial phenomena on the internal lee waves generation in the Strait of Gibraltar - José J. del Alonso Rosario; M. Arias Ballesteros; P. Villares Durán (Stochastic Environmental Research and Risk Assessment, 2007)

Movement of a South American perch Percichthys trucha in a mountain Patagonian lake during spawning and prespawning periods - L. Buria; S. J. Walde; M. Battini; P. J. Macchi; M. Alonso; D. E. Ruzzante; V. E. Cussac (Journal of Fish Biology, 2007)
Movement of the South American perch Percichthys trucha (Perciformes: Percichthyidae) was studied in a set of interconnected mountain lakes in northern Patagonia. Fish were tracked using attached acoustic tags and a fixed hydrophone array over two seasons, corresponding to the spawning (1999) and prespawning periods (2000). Percichthys trucha was found to move throughout the lake system, and to use a small, shallow, connected lake as a principal spawning area. In addition, detailed behavioural information was obtained for the spawning period. Most fish spent the initial 2 weeks descending from the littoral zone to depths of 5–8 m, presumably while feeding. Fish changed depth slowly, spending several days at each depth, and moving throughout the lake. A few days prior to the full moon, there was a change in behaviour thought to be associated with spawning, where the fish moved toward the vegetated littoral areas. Marked daily behaviour also began at this time, with movement to particular near‐shore locations at dusk, and return to slightly greater depths offshore at or before dawn. Study of the behaviour of P. trucha during the breeding season has highlighted the conservation significance of the main locations within the lake system.

Carbon isotope composition of fossil charcoal reveals aridity changes in the NW Mediterranean Basin - J. P. FERRIO; N. ALONSO; J. B. LÓPEZ; J. L. ARAUS; J. VOLTAS (Global Change Biology, 2006)
Although several proxies for the inference of precipitation have been proposed, evidence of changes in aridity during the Holocene is scarce, and most is only qualitative. Moreover, precipitation regimes show relatively poor spatial correlations and can exhibit contrasting responses to global climate trends in different areas. Thus, there is a need to concentrate efforts at the local scale in order to increase the spatial resolution of palaeoclimate records, especially regarding water availability in semiarid zones. We propose the analysis of carbon isotope composition ( δ 13 C) in fossil charcoal (routinely recovered from archaeological sites) to quantify changes in water availability in the past. We applied this approach to reconstruct variations in aridity during the last four millennia in the Ebro Depression (NE Iberian Peninsula). First, we studied the effect of carbonization over a range of temperatures (300–500°C) on the δ 13 C of Aleppo pine ( Pinus halepensis Mill.) wood cores, collected from nine locations in NE Iberian Peninsula with distinct water availability. Despite significant changes in δ 13 C caused by carbonization, the original climatic signal of wood δ 13 C was well preserved. Moreover, δ 13 C shifts induced by this process were successfully corrected by accounting for variation in charcoal carbon concentration (%C). After removing the effect of carbonization, we estimated annual precipitation ( P ) and the ratio between annual precipitation and evapotranspiration ( P / E ) from the δ 13 C of fossil charcoal. In general, estimated water availability in the past was higher than present values, indicating that latter‐day (semiarid) conditions are mostly due to recent climate changes. The good agreement between our findings and other evidence indicates that the analysis of δ 13 C in charcoal may be useful to expand current palaeoclimate records as it provides a complementary (and quantitative) source of information to assess climate dynamics.

Inhibition of infectious haematopoietic necrosis virus in cell cultures with peptide‐conjugated morpholino oligomers - M Alonso; D A Stein; E Thomann; H M Moulton; J C Leong; P Iversen; D V Mourich (Journal of Fish Diseases, 2005)
Delivery of phosphorodiamidate morpholino oligomers (PMO) into fish cells in vitro and tissues in vivo was examined. Uptake was evaluated by fluorescence microscopy and flow cytometry after treating cultured cells or live rainbow trout with 3′ fluorescein‐tagged PMO. Arginine‐rich peptide conjugated to the 5′ end of the PMO markedly enhanced cellular uptake in culture by 8‐ to 20‐fold compared with non‐peptide‐conjugated PMO as determined by flow cytometry. Enhanced uptake of PMO conjugated to peptide was also observed in tissues of fish treated by immersion. The efficacy of PMO as inhibitors of infectious haematopoietic necrosis virus (IHNV) replication was determined in vitro . Peptide‐conjugated PMOs targeting sequences within the IHNV genomic RNA (negative polarity) or antigenomic RNA (positive polarity) significantly inhibited replication in a dose‐dependent and sequence‐specific manner. A PMO complementary to sequence near the 5′ end of IHNV genomic RNA was the most effective, diminishing titre by 97%, as measured by plaque assay and Western blot. These data demonstrate that replication of a negative‐stranded non‐segmented RNA virus can be inhibited by antisense compounds that target positive polarity viral RNA, or by a compound that targets negative polarity viral RNA.

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Effects of Trochanteric Soft Tissues and Bone Density on Fracture of the Female Pelvis in Experimental Side Impacts - Brandon S. Etheridge; David P. Beason; Robert R. Lopez; Jorge E. Alonso; Gerald McGwin; Alan W. Eberhardt (Annals of Biomedical Engineering, 2005)

GENDER DIMORPHISM AND ALTITUDINAL VARIATION OF SECONDARY COMPOUNDS IN LEAVES OF THE GYNODIOECIOUS SHRUB Daphne laureola - CONCHITA ALONSO; RICARDO PREZ; PEDRO M. NIETO; JULIO DELGADO (Journal of Chemical Ecology, 2005)

Neoproterozoic?Cambrian synsedimentary magmatism in the Central Iberian Zone (Spain): geology, petrology and geodynamic significance - M. D. Rodrguez-Alonso; M. Peinado; M. Lpez-Plaza; P. Franco; A. Carnicero; J. C. Gonzalo (International Journal of Earth Sciences, 2004)

Genetic transformation of selected mature cork oak (Quercus suber L.) trees - R. lvarez; P. Alonso; M. Cortizo; C. Celestino; I. Hernndez; M. Toribio; R. J. Ords (Plant Cell Reports, 2004)

A case of urethritis due to Ureaplasma urealyticum associated with Lfgren?s syndrome - M. Lpez-Gmez; P. Gmez-Avivar; M. A. Lpez-Ruz; J. Jimnez-Alonso (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Pneumococcal bacteremia in children: an 8-year review in two hospitals in Barcelona - A. Prez; P. Sala; M. Gimnez; M. Sierra; A. Esteve; A. Alonso; M. Quesada; F. Raspall; V. Ausina; C. Rodrigo (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Human papillomavirus type 16 E5 protein colocalizes with the antiapoptotic Bcl-2 protein - E. Auvinen; A. Alonso; P. Auvinen (Archives of Virology, 2004)

Toxicity Identification Evaluation of Organic Pollutants Based on Solid-Phase Micro-Extraction and Gas Chromatography/Mass Spectrometry - C. Fernndez; C. Alonso; J. Pro; M. M. Babn; P. Garca; J. V. Tarazona; G. Carbonell (Bulletin of Environmental Contamination and Toxicology, 2004)

Competitive Retention of Lead and Cadmium on an Agricultural Soil - José M. Rodríguez-Maroto; Rafael A. García-Delgado; César Gómez-Lahoz; Carlos Vereda-Alonso; Francisco García-Herruzo; M. P. Pérez Muñoz (Environmental Monitoring and Assessment, 2003)

Expression of porcine CD163 on monocytes/macrophages correlates with permissiveness to African swine fever infection - C. Snchez-Torres; P. Gmez-Puertas; M. Gmez-del-Moral; F. Alonso; J.M. Escribano; A. Ezquerra; J. Domnguez (Archives of Virology, 2003)

Virulence of Infectious hematopoietic necrosis virus and Infectious pancreatic necrosis virus coinfection in rainbow trout ( Oncorhynchus mykiss ) and nucleotide sequence analysis of the IHNV glycoprotein gene - M. Alonso; S. Rodrguez Saint-Jean; S. I. Prez-Prieto (Archives of Virology, 2003)

The Concentrations and Bioconcentration Factors of Copper and Zinc in Edible Mushrooms - J. Alonso; M. A. Garca; M. Prez-Lpez; M. J. Melgar (Archives of Environmental Contamination and Toxicology, 2003)

Distribution of Metal Extractable Fractions during Anaerobic Sludge Treatment in Southern Spain WWTPs - G. J. Solís; E. Alonso; P. Riesco (Water, Air, & Soil Pollution, 2002)

Predator associated morphology in Galaxias platei in Patagonian lakes - D. Milano; V. E. Cussac; P. J. Macchi; D.E. Ruzzante; M. F. Alonso; P. H. Vigliano; M. A. Denegri (Journal of Fish Biology, 2002)
Among 158 Galaxias platei individuals, collected from nine deep Andean lakes and from one shallow lake on the Patagonian steppe, morphological characters associated with caudal fin length were negatively correlated with predation intensity as measured by the incidence of piscivory. Fish from lakes with high rates of piscivory had relatively short caudal fins and those from lakes with low piscivory had long caudal fins. It is hypothesized that in this species caudal fin length affects swimming ability and thus, ability to escape from predators. The population of G. platei from Lake Espejo with an intermediate level of piscivory contained individuals with both long and short caudal fins. Morphological variation within this lake was related to the exploitation of food resources and habitat; individuals with shorter tails ate more amphipods and inhabited shallower habitats. The results indicated that while the among‐lakes morphological variation in G. platei was influenced largely by differences in predation intensity, within‐lake morphological variation, where predation was intermediate, appeared to be affected by both predation and differences in the exploitation of food resources.

Toxicity of Linear Alkyl Benzenes (LABs) to the Aquatic Crustacean Daphnia magna through Waterborne and Food Chain Exposures - C. Fernández; C. Alonso; P. García; J. V. Tarazona; G. Carbonell (Bulletin of Environmental Contamination and Toxicology, 2002)

Biochemical Responses of Pinus pinaster Trees to Fire-Induced Trunk Girdling and Crown Scorch: Secondary Metabolites and Pigments as Needle Chemical Indicators - M. Alonso; M. J. Rozados; J. A. Vega; P. Pérez-Gorostiaga; P. Cuiñas; M. T. Fontúrbel; C. Fernández (Journal of Chemical Ecology, 2002)

C and Sr isotopic evolution of carbonate sequences in NW Argentina: Implications for a probable Precambrian-Cambrian transition - A. N. Sial; V. P. Ferreira; A. J. Toselli; F. G. Aceñolaza; M. M. Pimentel; M. A. Parada; R. N. Alonso (Carbonates and Evaporites, 2001)

Antigenic and immunogenic properties of a chimera of two immunodominant African swine fever virus proteins - M. G. Barderas; F. Rodríguez; P. Gómez-Puertas; M. Avilés; F. Beitia; C. Alonso; J. M. Escribano (Archives of Virology, 2001)

Cytological study and immunohistochemical location of PSP toxins in foot skin of the ormer, Haliotis tuberculata , from the Galician coast (NW Spain) - I. Bravo; J. M. Franco; A. Alonso; R. Dietrich; P. Molist (Marine Biology, 2001)

Clinical Evaluation of an In-House IS 6110 Polymerase Chain Reaction for Diagnosis of Tuberculosis - J. Almeda; A. García; J. González; L. Quintó; P. J. Ventura; R. Vidal; G. Rufí; J. A. Martínez; M.T. Jiménez de Anta; A. Trilla; P. L. Alonso (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

In Vitro Activity of a New Liposomal Nystatin Formulation Against Opportunistic Fungal Pathogens - G. Quindós; A. J. Carrillo-Muñoz; M. T. Ruesga; R. Alonso-Vargas; Y. Miranda; C. Tur-Tur; M. Rubio; T. L. Wallace; P. A. Cossum; E. Martín-Mazuelos; R. Cisterna; J. Pontón (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Connexin 43 expression is downregulated in raft cultures of human keratinocytes expressing the human papillomavirus type 16 E5 protein - P. Tomakidi; H. Cheng; A. Kohl; G. Komposch; A. Alonso (Cell and Tissue Research, 2000)

STOMACH CONTENTS OF FALSE KILLER WHALES ( PSEUDORCA CRASSIDENS ) STRANDED ON THE COASTS OF THE STRAIT OF MAGELLAN, TIERRA DEL FUEGO - Mariano Koen Alonso; Susana N. Pedraza; Adrian C. M. Schiavini; R. NATALIE P. Goodall; Enrique A. Crespo (Marine Mammal Science, 1999)
A bstract We examined the stomachs of 25 false killer whales collected from a mass stranding of 181 animals along both coasts of the Strait of Magellan, Chile, in March 1989. The 21 stomachs (nine males and 12 females), with food remains contained 11 prey species (nine cephalopods and two fishes) with a total of 442 individuals. Except for one case, food remains were meager, indicating that the animals had not eaten for some time or through stress had vomited on the beach. Eleven of the 21 animals had mud (often with squid beaks) in the esophagus and first stomach. The prey were identified employing squid beaks, fish otoliths and bones, and their wet weights were estimated using regressions between hard parts and known weights of species. The most important prey were the oceanic and neritic‐oceanic squids, Martialia byadesi and Illex argentinus , followed by the neritic fish, Macruronus magellanicus . Of less importance were the oceanic squid, Todaroes fillipovae , the oceanic and epipelagic octopus, Ocytboe sp. , and the oceanic squid, Moroteuthis ingens . The rest of the prey were poorly represented and included four oceanic squids and one neritic fish. The prey species of these animals were subantarctic, with two antarctic species, abundant over the Patagonian shelf and adjacent oceanic waters around Tierra del Fuego.

Prospective Study of Streptococcus milleri Hepatic Abscess - J. Corredoira; E. Casariego; C. Moreno; L. Villanueva; M. J. López Alvarez; J. Varela; A. Rodríguez; P. Alonso; A. Coira (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Clinical Evaluation of a Commercial Ligase-Based Gene Amplification Method for Detection of Mycobacterium tuberculosis - P. Alonso; A. Orduña; M. A. Bratos; A. San Miguel; A. Rodríguez Torres (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Prospective study ofStreptococcus milleri hepatic abscess - J. Corredoira; E. Casariego; C. Moreno; L. Villanueva; M. J. López Alvarez; J. Varela; A. Rodríguez; P. Alonso; A. Coira (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Clinical evaluation of a commercial ligase-based gene amplification method for detection ofMycobacterium tuberculosis - P. Alonso; A. Orduña; M. A. Bratos; A. San Miguel; A. Rodríguez Torres (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

The Cystatin S gene maps to rat Chromosome 3, to which Dlmgh18 is re-assigned from Chromosome 1 - M. Beatriz Duran Alonso; Paul Shiels; Andrew S. McCallion; Neil K. Bennett; Anthony P. Payne; Josiane Szpirer; Claude Szpirer; Martin J. Brodie; R. Wayne Davies; Roger G. Sutciffe (Mammalian Genome, 1997)

The cervical cancer screening program in Mexico: problems with access and coverage - E. C. Lazcano-Ponce; P. Najera-Aguilar; E. Buiatti; P. Alonso-de-Ruiz; P. Kuri; L. Cantoral; M. Hernandez-Avila (Cancer Causes & Control, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Sequence of the coding regions from the 3.0 kb and 3.9 kb mRNA - P. Britton; C. Lopez Otin; J. M. Martin Alonso; F. Parra (Archives of Virology, 1989)

Glucose and fructose consumption in a phosphoglucoseisomeraseless mutant in Saccharomyces cerevisiae - Carlos Pascual; Alberto Alonso; Celso Prez; Luis S. Herrera (Archives of Microbiology, 1979)